Blending Ratio Analysis of Akund/Cotton Blended Yarn Based on Micro Projection - 蒋晓 王芹 俞建勇 程隆棣 STOJANOVSKA Elena 范雯红 (东华大学学报（英文版）, 2012)
A microscope method was developed for testing the blending ratio of akund/cotton blended yarns. Fiber characteristics such as diameter, longitudinal feature, and hollow structure were observed to identify akund and cotton. Therefore, the measurement of the blending ratio for akund/cotton blended yarns based on each fiber＇ s amount, moisture regain, and metric count was available. The results show that using specimen＇ s longitudinal section is more effective during the fiber counting than specimen＇ s transverse section beuefitin~ from the separation of the fibers.